Geomorphology and surficial geology of the Femmilsjøen area, northern Spitsbergen - Allaart, Lis; Schomacker, Anders; Håkansson, Lena; Farnsworth, Wesley R.; Brynjólfsson, Skafti; Grumstad, Andreas; Kjellman, Sofia Elisabeth (Geomorphology, 2021)
Climate change is amplified in the Arctic, and establishing baseline data for its current character is important. Here we present a map of the geomorphology of the Femmilsjøen area, Spitsbergen, northern Svalbard. The regional physiography is characterised by a low-relief, high elevation mountain plateau, its high-relief steep slopes, and low-relief coastal lowlands. The results indicate that glaciers were most likely warm-based and erosive in the low terrain, whereas there are signatures of colder, less erosive ice on the plateaus during the Late Weichselian. Our study highlights the ongoing glacial and periglacial morphological processes in an area of hard and weathering-resistant bedrock, situated in northern Svalbard.